IMPLEMENTASI PERDA NOMOR 13 TAHUN 2012 TENTANG RETRIBUSI JASA USAHA PELAYANAN PELABUHAN DI KABUPATEN KEPULAUAN MERANTI - Silvani "; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
District Regulation Meranti Islands No. 13 of 2012 on Business Service Fees Ports that have been issued are expected to increase regional revenue originating from retribution withdrawal harbor, but since published in 2012 and held until 2015 had never withdrawal levy derived from port services achieve the targets set. This study aims to investigate the implementation of Regulation No. 13 Year 2012 regarding Business service levies Port Services and analyze the factors that affect the implementation of regional policy (Regulation No. 13 of 2012) Meranti Islands District.This study uses qualitative research methods with descriptive research, which can be interpreted as a problem-solving process was investigated by describing the state of the research subjects were based on the facts that appear during the study were then followed by the popularity of existing theories. Implementation of Regional Regulation (Perda) No. 13 of 2012 in implementation has not run optimally. Factors inhibiting the low / lack of socialization, community participation, and resources are low.Keywords: Implementation, Levy, Local Revenue